Sensor-Based Technology: Bringing Value to People with Diabetes and the Healthcare System in an Evolving World - Glennie JL; Berard L; Levrat-Guillen F (Dove Medical Press, 2022)
Judith L Glennie,1 Lori Berard,2 Fleur Levrat-Guillen3 1J.L. Glennie Consulting Inc., Aurora, Ontario, Canada; 2Nurse Consultant, Pink Pearls Inc, Winnipeg, Manitoba, Canada; 3Abbott Diabetes Care, Maidenhead, UKCorrespondence: Fleur Levrat-Guillen, Abbott Laboratories Ltd, Abbott House, Vanwall Business Park, Maidenhead, Berkshire, SL6 4XE, UK, Tel +44 7584108032, Email fleur.levrat@abbott.comPurpose: Evidence demonstrates that glucose-sensing technologies have enabled effective glycemic control for adults and children with type 1 diabetes (T1DM) or adults with type 2 diabetes (T2DM) on insulin therapy or non-insulin therapy. Here, we report on the wider value of glucose-sensing technology from the perspectives of person living with diabetes (PWD), healthcare providers (HCPs), and healthcare policy stakeholders.Methodology: Literature searches were conducted to identify published records and analysis, including across various healthcare organizations and agencies, of the impact of the FreeStyle Libre® flash glucose monitoring system in diabetes. These findings were combined with the outcomes of three healthcare attitudes surveys among PWD and diabetes healthcare professionals in Canada, including two commissioned for this purpose.Results: Clinical trials data and real-world evidence have proven the benefits of the FreeStyle Libre system on limiting hypoglycemia, lowering HbA1c, optimizing metrics of glucose control and reducing hospital admissions. These benefits are accompanied by improvements in patients' quality of life, work productivity, and savings to the health system. The FreeStyle Libre system has created an opportunity to change the organization and delivery of care, including during COVID-19 restrictions on access to standard care, thus generating system-wide benefits in addition to those accrued by patients and HCPs.Conclusion: Evidence-based improvements in glucose control for PWD using flash glucose monitoring are accompanied by increased treatment satisfaction and quality of life. Telemedicine with such remote monitoring systems increases the opportunities for simultaneous review of glucose data with HCPs and shared decision-making, thus encouraging adherence with treatment.Keywords: glucose monitoring, telemedicine, healthcare costs, organization of care, treatment adherence